1995
DOI: 10.1084/jem.182.4.931
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 and T helper type 2 cells are required for development of experimental onchocercal keratitis (river blindness).

Abstract: SummaryInflammation of the corneal stroma (stromal keratitis) is a serious complication of infection with the nematode parasite Onchocerca volvulus. Because stromal keratitis is believed to be immunologically mediated in humans, we used a murine model to examine the role ofT cells and T helper cell cytokines in the immunopathogenesis of these eye lesions. BALB/c mice immunized subcutaneously and injected intrastromally with soluble O. volvulus antigens (OvAg) developed pronounced corneal opacification and neov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 53 publications
7
82
1
Order By: Relevance
“…103,104 A strong Th2 response has been implicated, with release of IL-4, IL-5, IFN-γ, IgG 1 , and IgE. [105][106][107] More recently, attention has focused on the fact that O. volvulus maintains an endosymbiotic relationship with Wolbachia bacteria and that microfilaria release bacterial products which activate the immune response in human embryonic kidney cells and mice. 108,109 Microfilaria can invade the eye and stimulate both innate and adaptive immunity.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
See 1 more Smart Citation
“…103,104 A strong Th2 response has been implicated, with release of IL-4, IL-5, IFN-γ, IgG 1 , and IgE. [105][106][107] More recently, attention has focused on the fact that O. volvulus maintains an endosymbiotic relationship with Wolbachia bacteria and that microfilaria release bacterial products which activate the immune response in human embryonic kidney cells and mice. 108,109 Microfilaria can invade the eye and stimulate both innate and adaptive immunity.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…113,114 Eosinophil infiltration occurs later in the disease but aggravates the inflammatory response. 106,[114][115][116] However, neutrophil involvement is thought to be the driving factor behind the progressive corneal haze seen in onchocerciasis. 116 Fungi The most common agents in fungal infection are Fusarium spp.…”
Section: Onchocerca Volvulus (Onchocerciasis) Onchocerciasis Is Due Tmentioning
confidence: 99%
“…65 Also, sensitized CD4 þ T cells expressing IL-4 and IL-5 and but not IFN-g cells have been shown to play a role in the keratitis noted after injection with O. volvulus antigen. 66 Modulation of cytokines has been shown to affect the severity of keratitis in animal models. By using an IL-4 gene knockout model, a reduced inflammatory infiltrate with eosinophils was noted.…”
Section: Corneal Defenses To Infectionmentioning
confidence: 99%
“…Homologies to human onchocercal keratitis may only be hypothesized as human corneal samples for the investigation of pathology are scarce for obvious reasons. Previous studies using this murine model of Onchocerca keratitis demonstrated that (1) there is not only a predominant Th2 response, with elevated IL-4, IL-5, IgE, IgG1, and eosinophilia, but also an induction of IFNγ [10]; (2) the presence of endosymbiotic Wolbachia is essential for neutrophil recruitment to the corneal stroma and development of corneal haze [7]; (3) Wolbachia-induced corneal inflammation is TLR2 and MyD88 dependent [11,12]; and (4) dendritic cell activation and IFNγ production are dependent on TLR2, whereas Th2-associated responses (IL-5 production, eosinophil infiltration into the cornea) are TLR2 independent [13]. These findings are consistent with the hypothesis that Wolbachia induce Th1-associated responses and neutrophil recruitment through TLR2/MyD88-dependent responses, whereas Th2 responses are Wolbachia independent and may be induced directly by filarial antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular studies in human patients are scarce. Our laboratory previously established a mouse model of Onchocerca keratitis where repeat injections of filarial antigens induce the generation of an adaptive immune response similar to that of patients with generalized onchocerciasis [10]. The subsequent injection of filarial antigens into the corneal stroma induces migration of neutrophils and eosinophils, with lower numbers of macrophages and T cells infiltrating the corneal stroma.…”
Section: Discussionmentioning
confidence: 99%